Implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) For Unliveable Houses in Lhokseumawe City - Aisyah, Ti (Journal of Governance, 2025)
: A healthy and liveable house is a basic need for society because it can improve the quality of life for its residents. Having a decent and comfortable home supported by a healthy and orderly environment is the dream of every individual, which plays an important role in improving the welfare of individuals and society. In Lhokseumawe City, Aceh Province, there are still many low-income people (MBR) who live in uninhabitable houses (RTLH). The local government responded to this through the Self-Help Housing Stimulant Assistance Program (BSPS), which aims to improve the quality of RTLH houses through a community self-help approach. This research aims to examine how the Self-Help Housing Stimulant Assistance Program (BSPS) is implemented and the obstacles to implementing the Stimulant Assistance Program (BSPS) in Lhokseumawe City. This research aims to examine how the Self-Help Housing Stimulant Assistance Program (BSPS) is implemented and the obstacles to implementing the Stimulant Assistance Program (BSPS) in Lhokseumawe City. This research uses descriptive qualitative methods with data collection techniques using observation, interviews, and documentation. Data analysis techniques use the Miles & Huberman Interactive Analysis model (Sirajuddin 2017), including data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the implementation of the BSPS program is only a type of program to improve the quality of housing suitability, but in implementation it still faces obstacles such as limited aid funds, lengthy bureaucracy, poor quality of materials, as well as indications of politicized practices and lack of coordination with the village government and lack of outreach to village communities. Nevertheless, the BSPS program is considered capable of improving the quality of life of the people. BSPS has the potential to become an important instrument in equalizing welfare and alleviating poverty based on decent and dignified housing.